Is flat rate pricing for unlimited alcohol consumption associated with problematic alcohol consumption patterns? A cross-sectional study with the Japan COVID-19 and Society Internet Survey - Hiroyasu Iso; Takahiro Tabuchi; Yoshifumi Sugiyama; Midori Takada; Aya Kinjo; Mami Wakabayashi (BMJ Open)
Objectives This study investigates the relationship between flat rate pricing for unlimited alcohol consumption in restaurants and bar and problematic alcohol consumption patterns identified by the Alcohol Use Disorders Identification Test (AUDIT) during the COVID-19 pandemic.Methods A cross-sectional study was conducted using data from the Japan Society and New Tobacco Internet Survey in February 2022. A total of 19 585 current drinkers (55% of drinkers were men, and the mean age was 48.3 years) were categorised based on AUDIT scores; non-problem drinking (an AUDIT Score of 0–7), problem drinking (an AUDIT Score of 8 or over), hazardous alcohol use (an AUDIT Score of 8–14) and probable alcohol use disorders (an AUDIT Score of 15 or over). A score of 2 or higher in the third question of the AUDIT is identified as binge drinking. The explanatory variable was the presence of using flat rate pricing for unlimited alcohol consumption in the previous 12 months during the COVID-19 pandemic (February 2021 to February 2022). The associations of using the flat rate pricing with the problem or binge drinking, and with hazardous alcohol use or probable alcohol use disorders were analysed.Results People who used flat rate pricing during the COVID-19 pandemic were likely to be problem drinking and binge drinking compared with non-users of flat rate pricing; the respective adjusted ORs were 4.64 (95% CI: 4.24 to 5.07) and 3.65 (95% CI: 3.33 to 4.00) through multivariable binary logistic regression. The users of the flat rate pricing were associated with hazardous alcohol use and probable alcohol use disorder; the adjusted relative risk ratios were 3.40 (95% CI: 3.06 to 3.77) and 8.58 (95% CI: 7.51 to 9.80) through multinomial logistic regression.Conclusions Overall, using flat rate pricing for unlimited alcohol consumption was associated with both binge drinking and problem drinking, including hazardous alcohol use and probable alcohol use disorders.